The General Education Act and the Pedagogy. Recovering and sign - Mayordomo Pérez, Alejandro (Historia y Memoria de la Educación, 2021)
This paper undertakes a historical overview of the pedagogical considerations and references that characterize the basic educational reform in Spain in 1970. To do so, the text offers a description and interpretation of technical, political and legal documentation. Additionally, it clarifies the contexts, orientations, innovations and shortcomings of the legislation, known as the Villar Palasi law. Basically, the author attempts to demonstrate the characteristics of the scientific rationality or technical model of the law and its reform. The article also addresses the lack of agreement between the pedagogy being defended, the social and cultural context, and the specific policies that needed to be introduced in order for the reform to achieve its objectives. And finally, this work tries to clarify the significance of this General Education Act in the educational history of Spain.